(untitled) (Research, Society and Development, 2022)
This article aims to gather likely answers that contribute to a better understanding of how the practice of physical activity can interact with the immune system and influence the infection and prognosis of COVID-19. This is a narrative literature review carried out in PubMed, LILACS and SCIENCE Direct databases, using descriptors in English (Physical activity/Prognosis/COVID-19). At the end, 50 articles were included in the review. Studies have shown some evidence that moderate exercise has the ability to prevent the risk of acquiring the COVID-19 infection, decreasing mortality, since it has the ability to boost the immune system. However, adaptations to the immune system’s responses to exercise depend on the intensity and duration of the type of exercise. It was seen that constantly inactive patients had a higher rate of hospitalization, ICU admission and mortality. It is also evident the importance of physical exercises in the rehabilitation process of patients, playing a positive role in the treatment of diseases of the respiratory system. Therefore, physical activity as a non-pharmacological protective approach can be an important strategy to reduce the symptoms and deaths caused by COVID-19, generating benefits in the immune and inflammation systems. In addition, it can be considered fundamental for a better confrontation of the current and future pandemics.